Macrostructural design of highly porous SiOC ceramic foams by preceramic polymer viscosity tailoring. Issue 1 (1st January 2022) - Li, Quan; Tsai, Chen-Chih; Scheffler, Michael; Joshi, Shiv; Bordia, Rajendra K.
Abstract: Highly porous SiOC ceramic foams with gradient or uniform macrostructures were obtained through polymer derived ceramic routes. Precuring of preceramic polymers and introduction of SiO2 powders were used to tailor precursor viscosity and hence SiOC foam macrostructure. Effects of polymer viscosity on porosity, pore size, pore distribution were investigated by light microscopy and micro-computed tomography techniques. SiOC ceramic foams. Foams from one unmodified precursor, showed pore size gradient with small pores located at bottom and large pores at the top. To address this non-uniformity, the viscosity of the precursor was increased by pre-curing the preceramic polymer, which resulted in decrease of the average pore size and improvement in pore size uniformity. For a different system with a self-foaming preceramic polymer, because of the simultaneous release of foaming gases and rapid increase in viscosity during crosslinking, the foam had non-uniform macrostructure with large pores and thick struts at the bottom. By addition of SiO2 fillers, the crosslinking reaction rate was reduced leading to homogeneous pore nucleation and uniform small pore size foams.